Medical waste management in Jember Regency Hospital - Prajnawita, Disny; Padmawati, Retna Siwi; Daniel (Universitas Gadjah Mada, 2023)
Purpose: This research aims to analyze medical waste management practices and factors influencing medical waste management in Jember Regency hospitals. Methods: This study employed a qualitative research design with a case study approach. Research data was obtained from the results of in-depth interviews and observations. The determination of research informants was conducted using purposive sampling, involving 16 informants. Data analysis used causal loop diagram (CLD) analysis and the importance-performance analysis (IPA) method. Results: Medical waste management activities in Jember Lung Hospital and Jember Klinik Hospital were generally good. However, some activities could have been more suitable, including sorting, storage, in-situ transportation, and temporary storage. The two hospitals already had incinerators, but the incinerators were damaged due to a lack of maintenance. Therefore, the final medical waste management activities of the two hospitals were carried out with a licensed third party, PT. Sagraha, PT. Wastec International and PT. Universal Eco Pacific. The causal loop diagram (CLD) analysis reveals that the budget availability factor plays a crucial role in supporting effective medical waste management activities, particularly in terms of facility and infrastructure availability, human resource availability, and SOP implementation. Additionally, the quality of human resources and hospital accreditation has a positive influence on suitable medical waste management activities. The importance-performance analysis (IPA) method identified the main priority scale that requires improvement, specifically the hospital staff's discipline. Conclusion: Medical waste management activities in the Jember Lung Hospital and Jember Klinik Hospital, in general, have followed the RI Minister of Health Decree Number 1204/Menkes/SK/X/2004 and PerMenLHK No. 56 of 2015. However, segregation activities were still not optimal, and medical waste containers were not equipped with an infectious symbol. Therefore, efforts to increase periodic monitoring and evaluation of officer performance can improve officer discipline through SOP.